2011
DOI: 10.3892/ijo.2011.1099
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy with or without low-dose interleukin-2 in advanced non-small cell lung cancer: results from a phase III randomized multicentric trial

Abstract: Abstract. Non-small cell lung cancer (NSCLC) is associated with IL-2-dependent cell-mediated immunodeficiency. As IL-2 is the main lymphocyte growth factor, a phase III randomized multicenter trial was conducted to evaluate the impact of subcutaneous low-dose IL-2 added to standard chemotherapy (CT) on overall survival (OS) in advanced NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
0
30
0
2
Order By: Relevance
“…Information of 43 ASCO abstracts were collected by their clinical trial numbers through Clinicaltrials.gov or Google Scholar. Finally, we included 20 clinical trials1720212227282930313233343536373839404142, 17 from database search and 3313538 from ASCO abstracts (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information of 43 ASCO abstracts were collected by their clinical trial numbers through Clinicaltrials.gov or Google Scholar. Finally, we included 20 clinical trials1720212227282930313233343536373839404142, 17 from database search and 3313538 from ASCO abstracts (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Survival data were extracted from all eligible trials. HRs of overall survival (OS) were reported directly in sixteen trials, but were estimated by median survival time of treatment group and control group for three trials274042. The remaining one trial only provided survival curve41, so HR was calculated through curve data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent phase II trial by Correale et al showed that the addition of IL-2 to chemotherapy (gemcitabine plus docetaxel) in patients with advanced NSCLC improved response rates (58.3% vs. 28.6%) with good tolerability (10). However, these findings were not replicated in a phase III randomized trial of IL-2 in combination with chemotherapy with a cisplatin doublet (11). These results were further challenged by a subsequent study reporting a 20% partial response and 50% stable disease among 20 advanced NSCLC patients when IL-2 was administered with the pineal neuro-hormone melatonin (12).…”
Section: Cytokinesmentioning
confidence: 65%
“…Významnou limitaci léčeb-ného využití cytokinů v protinádorové léčbě představuje relativně vysoká toxicita a nevýhodná farmakokinetika [2][3][4][5][6][7]. V léčbě plicního karcinomu byly nejčas-těji zkoumány interleukin 2 a interferon α a γ. Přestože ně kte ré cytokiny byly hodnoceny v klinických studiích fáze II a III, jejich přínos nebyl potvrzen, a tak nenalezly významnějšího uplatnění v léčbě NSCLC ani v léčbě SCLC [11][12][13][14][15].…”
Section: Cytokinyunclassified